Framing the rules of the game: preparing for the first irrigation season in the Sardar Sarovar Project - Shah, Tushaar (2003)
Research highlight based on a fieldwork by IWMI-Tata Research Team in forty villages of First Phase Command of Sardar Sarovar Project